Proactive defense strategies against net load redistribution attacks in cyber-physical smart grids - Zhang, Hang (Kansas State University, 2022)
Recent advances in the cyber-physical smart grid (CPSG) have enabled a broad range of new devices based on information and communication technology (ICT). An open network environment in CPSG provides frequent interaction between information and physical components. However, this interaction also exposes the ICT-enabled devices to a growing threat of cyberattacks. Such threats have been alerted by recent cybersecurity incidents, and the security issues have strongly restricted the development of CPSG. Among various CPS cybersecurity incidents, cyber data attacks invade the cyber layer to destroy data integrity. Through elaborately eavesdropping on the transferred measurement data, the attacks can mislead the state estimation (SE) while keeping stealthy to conventional bad data detection (BDD). Due to the SE being the critical function of CPSG control, the cyber data attacks may cause massive economic loss, power system instability, or even cascading failures. Therefore, this dissertation focuses on the detection of stealthy data integrity attacks. This dissertation first performs a thorough review of the state-of-the-art cyber-physical security of the smart grid. By focusing on the physical layer of the CPSG, this work provides an abstracted and unified state-space model in which cyber-physical attack and defense models can be effectively generalized. The existing cyber-physical attacks are categorized in terms of their target components. In addition, this work discusses several operational and informational defense approaches that present the current state-of-the-art in the field, including moving target defense (MTD), watermarking, and data-driven strategies. The challenges and future opportunities associated with the smart grid cyber-physical security is also discussed. Further, a real-time digital simulator, namely Typhoon HIL, is utilized to visualize the random MTD against false data injection (FDI) attacks. Given the review section as a background, a hidden, coordinated net load redistribution attack (NLRA) in an AC distribution system is proposed. The attacker's goal is to create violations in nodal voltage magnitude estimation. An attacker can implement the NLRA strategy by using the local information of an attack region and power flow enhanced deep learning (PFEDL) state estimators. The NLRA is modeled as an attacker's modified AC optimal power flow problem to maximize the attack impact. Case study results indicate the PFEDL-based SE can provide the attacker with accurate system states in a low observable distribution system where conventional lease square-based SE cannot converge. The stealthiness of the hidden NLRA is validated in multiple attack cases. The influence of NLRA on the distribution system is assessed, and the impact of attack regions, attack timing, and attack area size are also revealed. Next, this dissertation highlights that current MTD strategies myopically perturb the reactance of D-FACTS lines without considering the system voltage stability. Voltage instability induced by MTDs is illustrated in a three-bus system and two more complicated systems with real-world load profiles. Further, a novel MTD framework that explicitly considers system voltage stability using continuation power flow and voltage stability indices is proposed to avoid MTD-induced voltage instability. In addition, this dissertation mathematically derives the sensitivity matrix of voltage stability index to line impedance, on which an optimization problem for maximizing voltage stability index is formulated. This framework is tested on the IEEE 14-bus and the IEEE 118-bus transmission systems, in which sophisticated attackers launch NLRAs. The simulation results show the effectiveness of the proposed framework in circumventing voltage instability while maintaining the detection effectiveness of MTD. Case studies are conducted with and without the proposed framework under different MTD planning and operational methods. The impacts of the proposed two methods on attack detection effectiveness and system economic metrics are also revealed. Finally, this dissertation proposes utilizing smart inverters to implement a novel meter encoding scheme in distribution systems. The proposed meter encoding scheme is a software-based active detection method, which neither requires additional hardware devices nor causes system instability, compared with MTD and watermarking. By elaborately constructing the encoding vector, the proposed smart-inverter-based meter encoding can mislead the attacker's SE while being hidden from alert attackers. In addition, by utilizing the topology of radial distribution systems, the proposed encoding scheme encodes fewer meters than current schemes when protecting the same number of buses, which decreases the encoding cost. Simulation results from the IEEE 69-bus distribution system demonstrate that the proposed meter encoding scheme can mislead the attacker's state estimation on all the downstream buses of an encoded bus without arousing the attacker's suspicion. FDI attacks constructed based on the misled estimated states are highly possible to trigger the defender's BDD alarm.
Keywords: Cyber-physical security; False data injection attack; Moving target defense; Voltage stability; Meter encoding; Smart grid